2017
DOI: 10.1016/j.freeradbiomed.2016.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Risky repair: DNA-protein crosslinks formed by mitochondrial base excision DNA repair enzymes acting on free radical lesions

Abstract: Oxygen is both necessary and dangerous for the aerobic cell function. ATP is most efficiently made by the electron transport chain, which requires oxygen as an electron acceptor. However, the presence of oxygen, and to some extent the respiratory chain itself, poses a danger to cellular components. Mitochondria, the sites of oxidative phosphorylation, have defense and repair pathways to cope with oxidative damage. For mitochondrial DNA, an essential pathway is base excision repair, which acts on a variety of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Recently, the regulated induction of DSBs in mtDNA of a stable human cell line has been reported to drive the loss of mtDNA, likely through degradation of the damaged molecules [43]. Furthermore, the possible effect of increased TFAM-binding to the damage hot spots on the maintenance of mtDNA is supported by the recent paper by [44]. These authors reported how DNA repair attempts may sometime cause a more serious damage leading to the formation of a DNA-protein crosslink that might trap the repair enzyme on the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the regulated induction of DSBs in mtDNA of a stable human cell line has been reported to drive the loss of mtDNA, likely through degradation of the damaged molecules [43]. Furthermore, the possible effect of increased TFAM-binding to the damage hot spots on the maintenance of mtDNA is supported by the recent paper by [44]. These authors reported how DNA repair attempts may sometime cause a more serious damage leading to the formation of a DNA-protein crosslink that might trap the repair enzyme on the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the sites of ROS production and mtDNA location, which is principally attached to the matrix side of the inner mitochondrial membrane, overlap, and so mtDNA must be repaired under ROS “bombardment”, affecting DNA repair proteins and lowering the efficacy of DNA repair [49]. Moreover, such a situation creates an opportunity to form mtDNA-protein crosslinks mediated by ROS, which are one of, if not the most serious form of DNA damage [50]. Therefore, the maintenance of mtDNA can be crucial to the proper functioning of mitochondria and can play an important role in the pathogenesis of mitochondria- or ROS-related diseases.…”
Section: Generation and Regulation Of Ros By Mitochondriamentioning
confidence: 99%
“…However, systematic analysis of the dual localized genes can reveal alternative AUGs or non‐conventional mitochondrial targeting signals, which can be targeted by gene knock‐in to interrogate only the mitochondrial function. More focus should be put on the search for enzymes involved in DNA maintenance mechanisms that are necessitated by the nature of nucleic acid metabolism reactions, such as recombination or the repair of protein‐DNA crosslinks . The recent discovery of a mitochondrial isoform of tyrosyl‐DNA phosphodiesterase 2, capable of removing tyrosine‐DNA adducts, could represent the first example of the existence of these DNA repair mechanisms in mitochondria.…”
Section: Introductionmentioning
confidence: 99%